Photodynamic therapy for oral candidiasis in human clinical trials: an evidence-based analysis - Yao Lin; Jianfeng Ding; Yufu He; Manting Zhang; Jingqi Zhang; Haotian Zhong; Qinghua Liu; Junbing He (Photodiagnosis and Photodynamic Therapy)
Objectives: Traditional antifungal drug treatment (AT) often induce resistance that may limit their ability to eradicate oral candidiasis. This study aimed to evaluate the efficacy of photodynamic therapy (PDT) compared to AT in reducing Candida colony count or improving clinical outcomes in oral candidiasis. Methods: We searched relevant articles through Cochrane Library, Web of Science, and PubMed databases up to June 25, 2024. Randomized controlled trials (RCTs) or other clinical comparative studies assessing the effectiveness of single or adjunctive PDT, or conventional chemical therapies were included. Study outcomes were clinical response or the changes from baseline in Candida colony counts. Results: A total of 16 clinical trials, including 13 RCTs, were enrolled. The pooled results showed PDT and AT therapy for oral candidiasis have comparable efficacy in the overall response rate (RR=0.97, P = 0.540) and no significant difference in the complete response rate between them. PDT+AT had a higher curing rate than AT alone (RR=1.67, CI: 1.16–2.39, P = 0.005). The network meta‑analysis revealed that PDT+AT, PDT or AT alone improved the reduction of Candida colony counts compared to distilled water treatment. Moreover, PDT+AT was significantly more effective than either PDT or AT alone, and it was most likely to provide the greatest benefit in Candida clearance, followed by AT, PDT, chlorhexidine, and distilled water. There was no statistical difference in the improvement of Candida colony counts between the PDT and AT groups. Conclusions: PDT demonstrates comparable efficacy to AT in treating oral candidiasis and may serve as a promising alternative approach. Combining PDT with AT further improves cure rates and Candida reduction. Future large-scale, high-quality RCTs are warranted to confirm these findings.